FACTOR ANALYSIS AFFECTING THE CAUSE OF MATERNAL DEATH IN PADANG CITY 2017 - miftah amalia yasti (Universitas Fort De Kock, 2018)
Maternal Mortality Rate of Padang City in 2016 reached 20 deaths. 10 cases of maternal deaths due to 3 cases of bleeding, 2 infections and 5 cases of Hypertension in Pregnancy. The purpose of this research is to know what factors influence the cause of maternal death in Padang city in 2017.The research is Mixed Metodes with sequential explanatory design conducted on June 16 until July 15, 2017 in the working area of Puskesmas in Padang City, DKK Padang and KUA Kuranji. Data collection by interview using questionnaires and interview guides. Respondents were case mothers totaling 7 people and control of 4 puskesmas that had death and 1 puskesmas with no maternal deaths amounting to 42 respondents. The informants were 7 heads of puskesmas, program holders of KIA Puskesmas and DKK Padang, and head of KUA. Processing and quantitative analysis with univariate, bivariate and multivariate while qualitative data reduction, categorization and sintesisasi poured form of matrix and described form of narration.The results of research on education level, anemia status, history of complication, age, parity, pregnancy distance, standard 7T midwife care, KB use, decision making and mother referral have relationship to maternal death. Nutritional status, ANC visits and handling at the referral facility did not have a significant relationship to maternal deaths. The most influential variable on the incidence of maternal death is the standard 7T midwife care.Input, the determinants of education has affect maternal mortality. The process, the determinant between all health of both mother and child and ministry of religion programs has not run optimally. Output, close determinants of complications and all risk factors that exist occur because the quality of services provided is not optimal. It is expected that Puskesmas in Padang city run all health of both mother and child programs maximally. Cross-sectoral cooperation with ministry of religion, mother affection movement to be more implemented maximally and continuum of care can be done.